THE SYSTEM OF GOVERNMENT IN THE ANCIENT HITTITE KINGDOM (1680-1450 B.C.) - Shareef, Walat; Hassan, Aram (Humanities Journal of University of Zakho, 2025)
The structure of government in the ancient Hittite kingdom is an elementary and essential topic in the study of its history. The Hittites were among the first to establish a centralized state in Anatolia. They played an important role in the political and cultural developments of the ancient Near East. The ruling system in the Hittite Empire was distinguish by an enlightened administrative and political organization, enabling it to play with the great powers at that period, such as the Egyptian and Babylonian empires. This study look into nature of power in the Hittite state, focusing on the monarchy, which granted the king absolute powers of government. Despite the centralization of royal authority, two councils shared the management of state affairs with him: the Panku and Tulya. These councils played advisory and regulatory roles, but the final say in decision-making always rested with the king. This study briefly examines the political history of the ancient Hittite Empire and the various stages it went through. It also sheds light on the origins and development of administration within the Hittite state structure, presenting the administrative form and its role in managing the empire's affairs. The study also demonstrates the pivotal roles played by the army in organizing and administering the Hittite state. eventually, the study reviews Hittite laws and their impact on the administration of the kingdom, along with the role played by the courts in implementing these laws and ensuring the smooth running of the administrative system.